2017
DOI: 10.3390/app7090891
|View full text |Cite
|
Sign up to set email alerts
|

Precision Irrigation System (PIS) Using Sensor Network Technology Integrated with IOS/Android Application

Abstract: Abstract:One of the most important factors for successful agricultural production is the irrigation system in place. In this study, a precision irrigation system, which takes advantage of the various phases of plant growth, was developed and implemented using the sensor network technology integrated with IOS/Android. The amount of water in the soil was measured via sensors that were placed on certain points of the area to be irrigated. These sensors were placed near the root of the product. Data from sensors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…Furthermore, to get value out of the displayed information, some of the SAAs permit data input from the end-users. [9] Irrigation management Irrigation scheduling 2-tier iOS EVAPO [49] Irrigation management Evapotranspiration estimation 2-tier Android PIS [34] Irrigation management Soil moisture sensing 2-tier iOS, Android SoilWaterApp [27] Irrigation management Soil moisture monitoring 2-tier iOS RaGPS [56] Irrigation management Extraterrestrial solar radiation 1-tier Windows SmartIrrigation [79] Irrigation management Irrigation scheduling 2-tier iOS, Android Crop Water Stress [69] Irrigation management Vine water stress 2-tier Android pCAPS [32] Irrigation management Crop water needs 1-tier Android VitiCanopy [23,29,30] Irrigation management Plant water requirement 1-tier iOS, Android SmartfLAIr [11] Yield management Crop yield estimation 1-tier Android PETEFA [62] Geographic information systems Geo-referenced soil analysis 2-tier Android eFarm [86] Geographic information systems Geo-tagging land data 2-tier Android PAMS [85] Geographic information systems Managing farmland spatial data 2-tier iOS, Android, Windows AMACA [76] Farm machinery/tools Estimating machinery cost 2-tier iOS, Android Ecofert [15] Fertiliser management Crop fertiliser estimation 2-tier Android cFertigUAL [65] Fertiliser management Crop fertiliser estimation 2-tier Android BaoKhao [87] Fertiliser management Leaf colour estimation for N fertiliser…”
Section: -Tier Applicationsmentioning
confidence: 99%
“…Furthermore, to get value out of the displayed information, some of the SAAs permit data input from the end-users. [9] Irrigation management Irrigation scheduling 2-tier iOS EVAPO [49] Irrigation management Evapotranspiration estimation 2-tier Android PIS [34] Irrigation management Soil moisture sensing 2-tier iOS, Android SoilWaterApp [27] Irrigation management Soil moisture monitoring 2-tier iOS RaGPS [56] Irrigation management Extraterrestrial solar radiation 1-tier Windows SmartIrrigation [79] Irrigation management Irrigation scheduling 2-tier iOS, Android Crop Water Stress [69] Irrigation management Vine water stress 2-tier Android pCAPS [32] Irrigation management Crop water needs 1-tier Android VitiCanopy [23,29,30] Irrigation management Plant water requirement 1-tier iOS, Android SmartfLAIr [11] Yield management Crop yield estimation 1-tier Android PETEFA [62] Geographic information systems Geo-referenced soil analysis 2-tier Android eFarm [86] Geographic information systems Geo-tagging land data 2-tier Android PAMS [85] Geographic information systems Managing farmland spatial data 2-tier iOS, Android, Windows AMACA [76] Farm machinery/tools Estimating machinery cost 2-tier iOS, Android Ecofert [15] Fertiliser management Crop fertiliser estimation 2-tier Android cFertigUAL [65] Fertiliser management Crop fertiliser estimation 2-tier Android BaoKhao [87] Fertiliser management Leaf colour estimation for N fertiliser…”
Section: -Tier Applicationsmentioning
confidence: 99%
“…This would bring considerable benefit in high wage countries like Switzerland. Işik et al (2017) reported that precision irrigation system enables about 60% reduction in labor force.…”
Section: Assumptions and Scenario Definitionmentioning
confidence: 99%
“…Several WSN-driven applications are focused on characterizing soil moisture and temperature [4][5][6], relative air humidity [7], electrical conductivity [8], pH [9] and wind speed and direction [10]. These variables have been widely analyzed in research related to crops such as lavender, mint [11], walnut [12], cherry [13], rice [14], tomatoes, lettuce [9], corn [8,15,16], lemon [17], potatoes [10] and grapes [18].…”
Section: Introductionmentioning
confidence: 99%